Effectiveness of Prophylactic Antibiotic Administration in Preventing Surgical Site Infections in Abdominal Surgery – A Meta-Analysis of RCTs & Observational Studies - Cheema, Muhammad Ali; Somaraj, Meghna; Zahid , Maheen; Mahmood , Tayyab; Arshad, Azal; Baneen; Sohail , Areeba; Galal Hossameldin, Abdelrahman Mohamed; Rashid , Ibrahim; Saleh , Aboubaker (Indus Journal of Bioscience Research, 2025)
Background: Surgical site infections (SSIs) are a major postoperative complication in abdominal surgeries, contributing to increased morbidity, prolonged hospitalization, and healthcare costs. Prophylactic antibiotic administration has been widely recommended, yet clinical practices vary significantly, especially across different healthcare settings. Objective: This meta-analysis aims to evaluate the effectiveness of prophylactic antibiotics in preventing SSIs among patients undergoing abdominal surgeries, with a focus on timing (pre-operative vs. post-operative), study design, and country income classification. Methods: A systematic search of PubMed, Scopus, Web of Science, and Cochrane CENTRAL was conducted up to March 2024, including randomized controlled trials (RCTs) and observational studies. Studies reporting on antibiotic prophylaxis and SSIs in abdominal surgeries were included. Risk ratios (RRs) with 95% confidence intervals (Cis) were calculated using a random-effects model. Subgroup analyses were performed based on antibiotic timing, study design, and country income level. Risk of bias was assessed using the Cochrane RoB 2.0 and Newcastle-Ottawa Scale. Results: Three studies (n = 9,790) met inclusion criteria. Overall, prophylactic antibiotics were associated with a 30% relative reduction in SSI risk (RR = 0.70; 95% CI: 0.38–1.30), though not statistically significant (P = 0.26), with high heterogeneity (I² = 85%). Subgroup analysis revealed significant benefit in RCTs (RR = 0.54; 95% CI: 0.38–0.77; P = 0.0006) and with pre-operative administration (RR = 0.54; 95% CI: 0.38–0.77; P = 0.0006), while post-operative use showed no benefit (RR = 1.04; 95% CI: 0.93–1.16; P = 0.48). Conclusion: Prophylactic antibiotics, especially when administered pre-operatively, are effective in reducing SSIs following abdominal surgery. Timing and study design significantly influence outcomes. These findings support current global guidelines and emphasize the need for standardized practices, particularly in low-resource settings. Further high-quality RCTs are recommended to enhance generalizability and inform global surgical protocols.